Changing Public Attitudes on Governments and Taxes (Tufts Archival Research Center, 2007)
Summary of the Advisory Commission on Intergovernmental Relations' 12th annual survey of public attitudes toward government and taxes. Asks eight questions on government revenues and spending and one on political parties and interest groups. Finds that sales taxes are favored if a tax increase is needed. Discusses regional patterns, opinions towards tax reform, ratings of governments, state responsibility, and attitudes towards political representation. Includes detailed results of the survey.